Futurescapes: expectations in Europe for relative effectiveness evidence for drugs in 2020. (August 2015) - Towse, Adrian; Garau, Martina; Mohr, Penny; Messner, Donna A
Aim: Explore key factors influencing future expectations for the production of evidence of relative effectiveness (RE) for drugs in Europe in 2020; construct three plausible future scenarios for RE evidence generation.Materials & methods: Semi-structured key informant interviews and three rounds of modified Delphi to gather expert perspectives and develop future scenarios.Results & conclusion: Most influential factors were degree of regulator use of postmarketing authorization (postlaunch) efficacy studies and adaptive licensing; degree of pan-European health technology assessment body coordination in reviewing prelaunch evidence and demanding postlaunch studies; the nature of regulator – health technology assessment body interaction. The most likely scenario entailed some change with postlaunch regulatory studies driving the likely nature of RE evidence generated.